The Train That Had Wings Selected Stories of M. Mukundan - Mukundan, M. (University of Michigan Press, 2020)
The Train That Had Wings presents modern life in Kerala in terms of a shared but tragically compromised humanity. Mukundan dares to look beneath the routines and facades of everyday life in order to probe depth of sin, greed, and hypocrisy but also to rediscover what brings joy and hope. Sixteen short story translations and a critical introduction, offering examples of Mukundan's realistic, existentialist, psychedelic, and parabolic stories, show his range and talent for the very short story. If Hawthorne wrote "twice told tales," Mukundan writes half-told tales, stories that jump in the middle, stomp around for just a minute, and leap away almost before the reader can settle in. Half-told, but a powerful and infectious half.